The Synthesis of Polymeric Nanospheres and the Application as High-Temperature Nano-Plugging Agent in Water Based Drilling Fluid - Li, He; Lv, Kaihe; Huang, Xianbin; Lu, Zhen; Dong, Xiaodong (Frontiers in Chemistry, 2020)
Nanoscale plugging agent is essential to wellbore stability of troublesome shale formation in the drilling of oil and gas wells. In this paper, polymeric nanospheres (PNS) with a double cross-linked structure were synthesized using monomers of styrene (ST), acrylamide (AM), 2-Acrylamide- 2-methylpropanesulfonic acid (AMPS) and dimethyl diallyl ammonium chloride (DMDAAC). PNS were characterized by FTIR, SEM and TGA. The plugging performance of PNS was analyzed using nitrogen adsorption experiments and SEM. And compatibility with water based drilling fluid (WBM) was studied. Experimental results showed that PNS had a mean particle size of 133 nm, and could retain about half of the original size after high temperature treatment under 150-200℃. TGA showed that the initial decomposition temperature of PNS is around 315°C. After plugging by PNS, both the specific surface area and pore volume of the shale cuttings decreased substantially compared with those of shale samples treated with water. Thus, PNS was thermal stable in WBM under high temperature and could effectively plug shale pores. Besides, PNS was beneficial to reduce both API and HTHP fluid loss of WBM.